(untitled) (American Journal of Research in Humanities and Social Sciences, 2026)
Coronary artery disease (CAD) remains one of the leading causes of morbidity and mortality worldwide, particularly among elderly patients with multiple metabolic comorbidities. Obesity and type 2 diabetes mellitus significantly aggravate the course of CAD and chronic heart failure (CHF) by affecting myocardial metabolism, microcirculation, and oxygen delivery to tissues. Objective: To evaluate the oxygen delivery index (DO₂I) in elderly women with CAD and advanced chronic heart failure (NYHA class III-IV) in the presence of obesity and type 2 diabetes. Methods: A prospective observational cross-sectional study was conducted including 35 women with CAD and CHF class III-IV who were admitted for coronary artery bypass grafting at the Republican Specialized Scientific and Practical Medical Center of Surgery named after Academician V. Vakhidov between January and May 2025. Patients were divided into two groups: CAD+CHF+obesity (n=17) and CAD+CHF+obesity+type 2 diabetes (n=18). A control group consisted of 12 age-matched women without CAD, obesity, or diabetes. Clinical, laboratory, and echocardiographic parameters were assessed. Oxygen delivery index was calculated using the formula DO₂I = 1.34 × Hb × SaO₂ × CI. Results: Although hemoglobin levels were comparable between groups, patients with combined obesity and type 2 diabetes demonstrated a significantly lower oxygen delivery index compared with patients with obesity alone (377.5±19.1 vs 437.9±27.7 ml/min/m², p<0.05). Correlation analysis revealed a moderate positive association between DO₂I and hemoglobin levels (r=0.531), heart rate